Development of a method and determination of requirements for reliability indicators of channels and modules of an active phased antenna array - Козачук, Оксана Дмитрівна; Костановський, Валерій Вікторович; Мачалін, Ігор Олексійович; Терентьєва, Ірина Євгенівна (Science-based technologies, 2020)
The study of reliability models of AFAR with one-level and two-level SSR was carried out. In this article, we propose the method for determining the requirements for the reliability indicators of channels and modules of the active phased antenna array to ensure the specified reliability of the antenna array. Requirements for the mean time to failure of the transceiving microwave subarray module and the secondary power supply module are presented in relation to the mean time to failure of the transceiving microwave channel. The example of determining the requirements for the mean time to failure of a transceiving AESA for an exponential distribution and composition of diffusion non-monotonic and exponential distributions (50% sudden and 50% gradual failures) is considered. The requirements for reliability are determined under the condition of the permissible decrease in the maximum range of the radar on value of 10%, which corresponds to 20% of the permissible failures of the transceiving channels